The Development of a Project-Based Science Creative Learning (SCL) as a Learning Proponent of Student PAUD Dehasen Bengkulu University - Partikasari, Rika; Nurwita, Syisva (International Journal for Educational and Vocational Studies, 2019)
Early childhood Education Programs (PAUD) learning is currently starting to develop and diversify.  Looking at the needs and curriculum nowadays we know that many PAUD schools have used K13 in their learning. The K13 PAUD learning strategy usually leads to a scientific approach. So, it needs to be designed in such a way as a learning strategy that implements supporting models in learning. The purpose of this reserach is to produce an effective development product in the form of a project-based Science Creative Learning (SCL) model as a learning proponent of PAUD students at Dehasen University Bengkulu. The research methode used in this research was Research and Development (R&D) then proceed with the effectiveness test in the classroom by quasi experiment. The results of the research are obtained a textbook which is a product of the development model of the project-based Science Creative Learning (SCL) that can be used as a learning proponent for students of PAUD UNIVED BENGKULU. The textbook has been revised and validated by experts. The effectiveness of the use of textbooks in learning can be seen from the differences in learning outcomes of students of PAUD DEHASEN BENGKULU UNIVERSITY who use textbooks (experimental groups) with those who do not use textbooks (control groups). For the experimental group the lowest score was 67 and the highest was 100. Whereas for the control group the lowest score was 58 and the highest was 83.